Floristics and structure of the remnant forests of the Obafemi Awolowo University campus, Ile-Ife Nigeria and their potential for conservation (1997)
The floristic composition and the girth sizes of the woody plants in seventeen sample forest plots at the Obafemi Awolowo University, Ile-Ife, Nigeria were studied with a view to making recommendations on the conservation of the forest. The 120 species found are those typical of drier lowland forest of southern Nigeria. Twenty-six species occurred in 8 of the 17 plots while 28 occurred in one plot each and could be regarded as rare. About 70% of the stems are less than 30 cm girth at breast height, an indication of recent disturbance. Brachystegia eurycoma dominated the ≥ 120 cm girth class and was found on hilly slopes that were suitable for farming. The benefits of conservation of the Campus forest include protection of an important watershed and teaching and research.